Project-based vs. Game-based learning: Which better improves critical thinking of elementary school students? - Wina Puspitasari; Peduk Rintayati; Moh Salimin; Anang Ma'ruf (Journal of Educational Management and Instruction (JEMIN), 2026)
The development of critical thinking skills among elementary school students remains a pressing issue, particularly in contexts where traditional teacher-centered approaches still dominate learning practices. This study aims to examine and compare the effectiveness of Project-Based Learning (PjBL) and Game-Based Learning (GBL) in improving students’ critical thinking skills in science. A quasi-experimental design with a nonequivalent control group was employed, involving 82 sixth-grade students from three public elementary schools, divided into PjBL (n = 44), GBL (n = 38), and control groups. Data were collected using pretest and posttest instruments based on Ennis’s critical thinking indicators and analyzed through normality and homogeneity tests, paired and independent sample t-tests using SPSS. The findings revealed that both PjBL and GBL significantly improved students’ critical thinking skills compared to conventional learning (p < .05). The PjBL group improved from 47.93 to 82.64, while the GBL group increased from 47.76 to 83.55, with GBL showing slightly higher gains. These results indicate that student-centered and interactive learning approaches are effective in fostering higher-order thinking skills. The study implies that integrating PjBL and GBL can enhance instructional quality and support the development of essential 21st-century competencies.